FENOMENA WAKAF PENDIDIKAN PESANTREN DI INDONESIA - Kopri Nurzen (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The discussion of this article begins with an explanation of the general provisions regarding waqf. Next, a brief description of waqf education in Islamic boarding schools in Indonesia is explained. Paid education schemes are the most dominant in it. At first glance, this seems to contradict the nature of waqf education as charity. Due to the high costs by the students, it gives the impression that the pesantren is a business institution. This paper explains the permissibility of waqf boarding schools to collect fees from students to maintain the continuity of education while maintaining that waqf does not become a business for personal, family and certain group interests. This paper also describes some of the phenomena that occur in the management of waqf pesantren, such as the impact of the lack of literacy of some pesantren managers regarding waqf and heirs suing pesantren waqf land. It was also stated that apart from paid pesantren, there are also pesantren in Indonesia which free their students from fees, because they are financed with productive endowments and assistance from donors.